Pemetaan Kelas Kesesuaian Lahan Untuk Budidaya Tambak Dengan Metode Skoring - Radhi Ariawan; Arfita Rahmawati (Infotekmesin, 2021)
Pond cultivation is a coastal sector’s potential in Nusawungu District. To optimize the potential of fish and shrimp ponds in Nusawungu District, mapping of the suitable coastal locations as pond cultivation areas was carried out. This research was included in descriptive – quantitative study of the suitability class of pond cultivation land by using the scoring method from the overlay parameter of land usage, soil type, soil texture, slope inclination, pond to river distance, and pond to beach distance. The land suitability class based on this method was divided into 3 (three) classes, suitable (S1), conditionally suitable (S2), and unsuitable (S3). The results showed that 48.32% or an area of 29.6008 km2, categorized S1 (suitable) as location for pond cultivation. Furthermore, the S2 (Conditionally suitable) class was recorded for 33.98% or an area of 20.8039 km2. S3 (unsuitable) class was recorded for 17.72% or an area of 10.8553 km2.